"Dream More, Learn More, Care More, and Be More": The Imagination Library Influencing Storybook Reading and Early Literacy. Issue 7 (3rd October 2018) - Waldron, Chad H.
Abstract: This study examined the free book giving program of Dolly Parton's Imagination Library and its influence upon storybook reading and early literacy within one county-wide setting in the United States. Family literacy and early literacy experiences are known to be critical to young children's literacy development. The study found that childre who received the Imagination Library books were statistically different from those children who did not participate in the free book giving program. This study has implications for the early literacy outcomes for young children and their families, as well as other communities who utilize Dolly Parton's Imagination Library.